Uma análise do ponto de vista em A Hora da Estrela e Laços de Família, de Clarice Lispector, e nas traduções italianas L'ora Della Stella e Legami Familiari - Cristina Mauri (2009)
This doctoral thesis belongs to the subarea of textual approaches to translation within the CORDIALL project (Corpus of Discourse for the Analysis of Language and Literature) carried out at LETRA (Laboratory for Experimentation in Translation), at Faculdade de Letras, UFMG. This subarea includes case studies focusing on the language of translationsand, particularly, on character and speech presentation in fiction. Continuing this tradition, this thesis studies point of view in translation by exploring a parallel corpus comprising the novel A hora da estrela (AHDE) and the collection of short stories Laços de família (LDF),both by Clarice Lispector, and their respective Italian translations L´ora della stella (LODS) and Legami familiari (LF) by Adelina Aletti. Aiming at contributing to the studies of point of view in translation, three purposes were outlined: (i) to analyze the fictional point of view in the source texts (STs) in order to detect typical writing patterns of the author both in the novel and the short stories; (ii) to observe writing patterns related to the fictional point of view in the target texts (TTs); and (iii) to investigate differences between the STs and the TTs in the construction of point of view. The theoretical framework of this thesis builds on studies onfictional point of view in translation and, as a prerequisite of the latter, on stylistics and speech and thought presentation studies. Literary criticism on Lispectors work was also resorted to in order to observe whether point of view features are said to be typical of Lispectors writing. Simultaneously, the descriptive set of Systemic-Functional Grammar wasfollowed as an aid to analyze some categories under investigation as well as the tools provided by Corpus Linguistics for methodological procedures. In order to achieve the purposes outlined here, four categories of linguistic indicators of fictional focalization wereanalyzed: deixis, free indirect speech, material Processes and modality. The major findings point out similar writing patterns in both AHDE-LDF and LODS-LF, although with a few frequency differences of the occurrences in each category. The differences observed in thetranslations regard all the four categories of analysis in both TTs, even though some specific differences were found just in LF. Such differences bring about dissimilarities in the construction of the fictional point of view, especially regarding the characters focalization. Furthermore, the analysis between the STs and the TTs led to questions other than thoseincluded in the initial purposes of this investigation such as the likely explicitation through the use of exclamations and interrogations.